205k views
0 votes
Evaluate the expression for the given values of the variables.- k2 – (2k – 5n) + 3n; k= - 3 and n= -5For k= - 3 and n= - 5, – k? - (2k – 5n) + 3n=).

1 Answer

5 votes

Answer

The answer is -43.

Step-by-step explanation

The question wants us to evaluate the expression using the given variables

-k² - (2k - 5n) + 3n

if k = -3, n = -5

So, to solve this, we would just substitute the given values for k and n

-k² - (2k - 5n) + 3n

= -(-3)² - [(2 × -3) - (5 × -5)] + (3 × -5)

= -(9) - [-6 - (-25)] - 15

= -9 - (-6 + 25) - 15

= -9 - (19) - 15

= -9 - 19 - 15

= -43

Hope this Helps!!!

User Shay Ben Moshe
by
6.5k points